Non‐coalescence and chain formation of droplets under an alternating current electric field. Issue 5 (21st January 2021) - Huang, Xin; He, Limin; Luo, Xiaoming; Xu, Ke; Lü, Yuling; Yang, Donghai
Abstract: The dynamic behaviors of two droplets and droplet cluster under an alternating current (AC) electric field are investigated. Two droplets generally undergo transformation from complete coalescence to partial coalescence and finally to non‐coalescence as the electric capillary number Ca p increases. The critical electric capillary number Ca pc for complete coalescence in the AC electric field remains unchanged and is twice as large as that in the direct current (DC) electric field when the frequency f ≥ 250 Hz. Charge transfer and reversal of electric field result in the reversal of the direction of electric force, which is the fundamental mechanism of non‐coalescence of two droplets and chain formation in droplet cluster. The number of rebounds dramatically increases as f increases, promoting the stability of droplet chain. The droplet chains in the high‐frequency AC electric field are longer and more stable than those in the low‐frequency AC electric field.